Rancang Bangun Destilator Elektrik dan Evaluasi Kinerja Destilasi Bioetanol dari Rumput Laut (Eucheuma Cottonii) - Fathan Edy Purwanto; Agus Dharmawan; Siswoyo Soekarno; Soni Sisbudi Harsono; Bambang Marhaenanto (Jurnal Teknologi Pertanian Andalas, 2022)
Bioethanol from seaweed is the ethanol produced from the anaerobic fermentation of seaweed with the assistance of microorganisms. A distillation process is required to separate ethanol from a mixture - the fermented bioproducts. The aims of this research are to develop a distiller equipped with a control system of temperature, evaluate the output flow rate and the content of bioethanol from seaweed (Euchemia cottonii). The desired electric distiller was developed in five main components, i.e., control system, heater, distilling tube, condenser, and a centrifugal pump. The seaweed is fermented with the starter Saccharomyces cerevisiae for 48 hours under room temperature. The fermented product is then distilled using a developed electric distiller for 6 hours; the control system worked to maintain the temperature in process, 800C. The distiller worked with an average output flow rate of 0.024 L/h. The bioethanol started to release from the system at a minute of 253 and temperature 710C. The output bioethanol had a yield of 3.3% dan 39% of alcohol content.